2004
DOI: 10.1183/09031936.03.00061703
|View full text |Cite
|
Sign up to set email alerts
|

The Arg753Gln polymorphism of the human Toll-like receptor 2 gene in tuberculosis disease

Abstract: Toll-like receptor 2 (TLR2), a member of the Toll-like receptor family, plays an important role in recognition of, and subsequent immune response activation against, mycobacteria. The genetic polymorphism of TLR2 (arginine to glutamine substitution at residue 753 (Arg753Gln)) has been associated with a negative influence on TLR2 function, which may, in turn, determine the innate host response to mycobacteria. The aim of the present study was to investigate the Arg753Gln single nucleotide polymorphism of the TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
280
4
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(306 citation statements)
references
References 30 publications
11
280
4
11
Order By: Relevance
“…We hypothesize that inefficient recognition of Map and failure in the subsequent innate and adaptive immune responses can be caused by defects in genes coding for TLR. TLR2 has been described as one of the main receptors for mycobacteria, and in humans, mutations in TLR2 have been detected and associated with higher susceptibility to tuberculosis (Lorenz et al, 2000;Kang and Chae, 2001;Ogus et al, 2004). After uptake, Map is able to evade the destructive processes by inhibition of phagolysosome fusion and is able to replicate inside the macrophages (Kuehnel et al, 2001;Hostetter et al, 2003;Weiss et al, 2004) and possibly also inside DC.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that inefficient recognition of Map and failure in the subsequent innate and adaptive immune responses can be caused by defects in genes coding for TLR. TLR2 has been described as one of the main receptors for mycobacteria, and in humans, mutations in TLR2 have been detected and associated with higher susceptibility to tuberculosis (Lorenz et al, 2000;Kang and Chae, 2001;Ogus et al, 2004). After uptake, Map is able to evade the destructive processes by inhibition of phagolysosome fusion and is able to replicate inside the macrophages (Kuehnel et al, 2001;Hostetter et al, 2003;Weiss et al, 2004) and possibly also inside DC.…”
Section: Introductionmentioning
confidence: 99%
“…12 There was no significant increase in the prevalence of the polymorphisms in the subjects with Q fever infection (Fisher's exact tests), indicating that these genetic variants are not associated with an increased risk of symptomatic Q fever. To assess the available power to detect a disease association of similar magnitude to previously published findings in comparable infectious diseases, with a set at 0.05 and our given sample size, we would have had 81% power to replicate the TLR2 association with pulmonary tuberculosis, 14 and 83% power to detect the association between the TLR4 single nucleotide polymorphisms (SNP) and Gram-negative sepsis. 15 Among the subjects with Q fever, the influence of each polymorphism on the severity of the acute illness (reflected by the symptom score) and duration of illness (reflected by the number of days with ongoing symptoms) was examined (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…5 However in the study reported here, no correlation was found between the level of Q fever-specific immunoglobulin G (IgG) production at 6 weeks or 12 months postenrolment, and the presence of either TLR-2 Arg753Gln or TLR-4 Asp299Gly polymorphic alleles (n ¼ 75), using the optical density to cutoff ratio in the enzyme-linked immunosorbent assay (ELISA) assay measuring anti-C. Figure 1 Cytokine production by LPS-stimulated PBMC. Ex vivo cytokine production was assessed as previously described, 14 by overnight incubation of PBMC with or without Salmonella typhimurium LPS (10 ng ml À1 ) before harvesting the supernatants and measurement of cytokine production (interleukin (IL)-1b, IL-2, IL-4, IL-6, IL-8, IL-10 IL-12, interferon (IFN)-g, tumor necrosis factor (TNF)) using a multiplex bead-based immunoassay (Bioplex, BioRad, Hercules, CA, USA). Sample collection and handling, as well as stimulation assays were conducted under endotoxinminimized conditions.…”
Section: Resultsmentioning
confidence: 99%
“…also been linked to a rare, heterozygous missense TLR4 mutation (Smirnova et al, 2003). The R753Q polymorphism in TLR2 is linked with reduced response to peptides from Borrelia burgdorferi and Treponema pallidum, and may predispose to Staphylococcal infection or tuberculosis (Ogus et al, 2004) while the R677W polymorphism in TLR2 which impairs activation of NF-B by Mycobacterium leprae and Mycobacterium tuberculosis apparently enhances susceptibility to leprosy and tuberculosis (Cook et al, 2004).…”
Section: Tlrs and Human Disease Processesmentioning
confidence: 99%